Oxybaphus himalaicus Mitigates Lipopolysaccharide-Induced Acute Kidney Injury by Inhibiting TLR4/MD2 Complex Formation - Honghong Zhan; Qingxiu Pu; Xiaoliang Long; Wei Lu; Guowei Wang; Fancheng Meng; Zhihua Liao; Xiaozhong Lan; Min Chen (MDPI AG, 2022)
Acute kidney injury (AKI) is described as the abrupt decrease in kidney function always accompanied by inflammation. The roots of Oxybaphus himalaicus Edgew. have long been used in Tibetan folk medicine for the treatment of nephritis. Nevertheless, modern pharmacological studies, especially about the underlying mechanism of O. himalaicus medications, are still lacking. Here, in lipopolysaccharide (LPS)-induced RAW264.7 macrophages, the O. himalaicus extract (OE) showed significant anti-inflammatory activity with the dose dependently reducing the LPS-stimulated release of nitric oxide and the mRNA level and protein expression of inflammatory cytokines and reversed the activation of nuclear factor kappa B (NF-κB). Co-immunoprecipitation assay indicated that OE inhibited Toll-like receptor 4/myeloid differentiation factor 2 (TLR4/MD2) complex formation and further suppressed both myeloid differentiation factor 88 (MyD88)-dependent and TIR-domain-containing adapter-inducing interferon-β (TRIF)-dependent cascades activation. In addition, OE could restrain NADPH oxidase 2 (NOX2) endocytosis by blocking TLR4/MD2 complex formation to prevent reactive oxygen species production. In LPS-induced AKI mice, OE treatment mitigated renal injury and inflammatory infiltration by inhibiting TLR4/MD2 complex formation. UPLC-MS/MS analysis tentatively identified 41 components in OE. Our results indicated that OE presented significant anti-inflammatory activity by inhibiting TLR4/MD2 complex formation, which alleviated LPS-induced AKI in mice.